ANALISIS FAKTOR PENYEBAB RENDAHNYA HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 15 PALEMBANG - Aisyah; Riswan Jaenudin; Dewi Koryati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
This research is analysist factor learning’s student that makes result low on economiclearning at SMA Negeri 15 Palembang The problem on this research was how the internal and eksternal factor make effect the learning’s outcome low to students class X at SMA negeri 15 palembang.The purpose of this study was to determine the factors that cause low yields of class X student at SMAN 15 Palembang. This research subject is class X.1, X.2 and X.3 comprising 118 students Sampling uses purposive sampling with the requirements of the required learning outcomes of students who KKM under 78 amount to 70 students. In this research conducted with supporting documentation as to complement the existing data in the field, distributing questionnaires to students, as well as interviews directly to economics teacher. Based on the conclusions the researchers can give advice to students in order to improve learning outcomes on economic subjects, teachers should use teaching methods that interest students, to further research if using a statement questionnaire should use language that facilitates students will have no difficulty in answering statement questionnaire.